Implementasi Etika Bisnis Islam Terhadap Pengalokasian Dana di Baitul Maal Wat Tamwil Bina Ummat Sejahtera Cabang Senori Tuban - Ana Nur Anisah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2020)
This study aims to determine the implementation of Islamic business ethics on the allocation of funds in the Baitul Maal Wat Tamwil Bina Umat Sejahtera (BMT BUS) Senori branch. Business ethics in allocating funds is very important for every financial institution, especially sharia. Because in allocating these funds must be done well and late so that the goals of the institute can be achieved. And Islamic business ethics must be applied in Islamic financial institutions as a form of implementation and responsibility of the Islamic ummah in carrying out Islamic law in muamalah. BMT BUS is one of the non-bank financial institutions engaged in savings and loans. The main activity is to collect and distribute funds from and to members in exchange for profit sharing from profit margins obtained by BMT from the sale and purchase mark up. The research uses qualitative methods with data collection methods using observation, interviews and documentation as well as descriptive qualitative data analysis methods. The results obtained can be concluded as follows: 1. The contract used at BMT BUS Senori is Murabahah and Mudharabah contract; 2. The allocation of funds in BMT BUS Senori so far is by collecting funds from the public in the form of savings and channeling them to the public in the form of financing; 3. The application of Islamic business ethics to the allocation of funds has been carried out in accordance with sharia business ethics as well as in accordance with its Standard Operational Procedure. Keywords: Business ethics, allocation of funds, Baitul Maal Wat Tamwil Bina Umat Sejahtera